"All That Glitters is Not Gold": Reflections on Javor Gardev’s Production of William Shakespeare’s "The Merchant of Venice" at The Bulgarian National Theatre - Niagolov, Georgi (English Studies at NBU, 2024)
The article reviews Javor Gardev’s recent production of Shakespeare’s The Merchant of Venice on the stage of the Bulgarian National Theatre in the context of the play’s long debated generic ambiguity and the “unpleasant” issues it confronts. It argues that even though, due to good historical reasons, the issue of antisemitism has attracted most of the attention so far, the central “unpleasant” issue in the original text is patriarchalism and the inequality between men and women. The play and the production’s divergent treatments of this issue are considered in the context of today’s antifeminist backlash, as well as the more general tendency to withdraw from traditional Western values, such as democracy, freedom, human rights. The current global and locally Bulgarian perspectives are discussed in order to demonstrate the urgency of taking a clear stand in support of these values.